Synthesis and Characterization of Banana and Pineapple Reinforced Hybrid Polymer Composite for Reducing Environmental Pollution - M. Ramesh; D. Jafrey Daniel James; G. Sathish kumar; V. Vijayan; S. Raja Narayanan; Aklilu Teklemariam (Bioinorganic Chemistry and Applications)
Nonbiodegradable polymers constitute major pollution and their usage cannot be ignored due to their properties. Hybrid polymer composite research has increased in recent times due to improved characteristics and biodegradable nature. The effect of different stacking sequences containing pineapple/banana/basalt fiber has been studied in the present work to reduce the usage of synthetic fibers without compromising on properties. Hybrid composites were manufactured using the hand layup method and were assessed for mechanical and morphological characteristics. The results showed that several properties improved by keeping the pineapple layer in the skin layer. The adhesion between the matrix and the fiber played a vital role in determining the properties of the composites manufactured. Morphological studies have concluded that the proper bonding between the matrix and the fiber has enhanced several properties.